2014
DOI: 10.1186/s12916-014-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

The Ariadne principles: how to handle multimorbidity in primary care consultations

Abstract: Multimorbidity is a health issue mostly dealt with in primary care practice. As a result of their generalist and patient-centered approach, long-lasting relationships with patients, and responsibility for continuity and coordination of care, family physicians are particularly well placed to manage patients with multimorbidity. However, conflicts arising from the application of multiple disease oriented guidelines and the burden of diseases and treatments often make consultations challenging. To provide orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
219
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(233 citation statements)
references
References 47 publications
6
219
0
8
Order By: Relevance
“…A first way to reconcile viewpoints could be to encourage better patient-physician collaboration in drug treatment. In the current context of managing multimorbidity in primary care, 27,28 patient-centered care with shared decision making seems to be a key to managing patient complexity 25,28,29 and to achieving minimally disruptive medicine. 30 Physicians have to reach an optimal patientphysician relationship, which requires good communication and may result in better health outcomes, 31 especially for medication adherence.…”
mentioning
confidence: 99%
“…A first way to reconcile viewpoints could be to encourage better patient-physician collaboration in drug treatment. In the current context of managing multimorbidity in primary care, 27,28 patient-centered care with shared decision making seems to be a key to managing patient complexity 25,28,29 and to achieving minimally disruptive medicine. 30 Physicians have to reach an optimal patientphysician relationship, which requires good communication and may result in better health outcomes, 31 especially for medication adherence.…”
mentioning
confidence: 99%
“…In some instances, one option may far outweigh the others, while others might be preferencesensitive (244,246). Preference-sensitive decisions, are those for which there is limited evidence informing the options; the benefits and harms of the provided options are similar; or the evidence does not favour one option over another (141,(247)(248)(249)(250)(251)(252). In these situations the preferences and priorities of the patient need to be considered, as the value placed on the expected benefits, harms and/or outcomes may differ across clinicians and patients, across patients faced with the same decision, and within patients over time (244,246,251,253).…”
Section: Patient-centred Carementioning
confidence: 99%
“…Subsequent authors (141,247,248,255) have identified similar components or steps, but central to all of these works is the focus on engaging and involving patients in decision-making processes. Of note is the emphasis on sharing information in order to achieve shared decision-making.…”
Section: Deciding On Treatment To Implementmentioning
confidence: 99%
See 2 more Smart Citations